Role of apoptosis in testicular tissue damage caused by varicocele - (:unkn) unknown (My University, 1998)
OBJECTIVE: Histomorphological changes reported in patients with varicocele (so-called stress pattern) have some degree of resemblance to the ones observed during apoptosis of various cell types due to a variety of reasons. In order to further clarify a possible role of apoptosis in impaired spermatogenetic activity associated with varicocele, we have investigated the presence of this specific type of cell death in testicular tissue. MATERIAL AND METHODS: Surgical specimens were obtained after the completion of ligation and division of the spermatic vein(s) in patients with varicocele associated with infertility and testicular tissue obtained by scrotal orchiectomy for hormonal ablation treatment in prostate cancer patients served as the control group. Terminal deoxynucleotidyl transferase end labeling (TUNEL) technique was utilized in paraffin-embedded tissue specimens to demonstrate the presence of apoptosis. RESULTS: Data obtained from 29 samples (varicocele, 24 patients; control, 5 patients) revealed that apoptosis was quite rare in testicular tissue of control group. Mean percentage of apoptotic cells per high power field (x400 magnification) was 2% for the control group and 14.7% for varicocele patients. CONCLUSION: In light of our data, it appears that apoptosis may have a significant role in spermatogenetic dysfunction associated with varicocele.
Keywords: Adult; Humans; Middle Aged; Aged; Adolescent; Male; Biopsy; Prostatic Neoplasms; Apoptosis; Orchiectomy; Testis; Varicocele; Histocytological Preparation Techniques